BIOPROSPEKSI RHIZOBAKTERI PENGHASIL IAA (Indole Acetic Acid) DARI TANAMAN JAGUNG (Zea maysL.) DI AREA PERTANIAN SEMI ORGANIK DESA BATURKEC. GETASAN KAB. SEMARANG - Khoirul Huda; Anto Budiharjo; Budi Raharjo (Jurnal Akademika Biologi, 2014)
Microorganisms in nature have a rich diversity and have an important role in human lives, especially in agriculture. Some types of bacteria live in the area of plant roots called rhizobacteria. Some rhizobacteria has the ability to stimulate the growth of crops such as produce IAA (Indole Acetic Acid). This study aims to find rhizobacteria in maize (Zea mays L.) which has the ability to produce IAA (Indole Acetic Acid) that can be used as a reference in rhizobacteria resource utilization to increase agricultural production in a sustainable and environmentally friendly.This study was conducted with bacterial isolation, characterization of bacterial isolates in colony and cell morphology, The test of rhizobacteria’s ability to produce IAA (Indole Acetic Acid), the molecular identification of the isolates were able to produce IAA rhizobacteria and confirmatory tests. The results of isolation obtained seventeen isolates of rhizobacteria where there is a one of isolate (J.6) is able to produce 20.5 ppm IAA in TSB (Tryptic Soy Broth) supplemented with 100 ppm of L-tryptophan. The Result of the molecular identification show that isolate which has the ability to produce IAA has 97% similarity with Bacillus safensis Strain A-2. Isolate “J.6” have the same characteristic features with Bacillus safensis. They are a gram-positive, rod-shaped, capable of forming endospores, motile, catalase positive, capable of fermenting glucose and hydrolyzing a starch. Key word : Rhizobacteria, Indole Acetic Acid, Bacillus safensis Strain A-2